General theory of Lie groupoids and Lie algebroids - Mackenzie Kirill C H (Cambridge CUP, 2005)
This is a comprehensive modern account of the theory of Lie groupoids and Lie algebroids, and their importance in differential geometry, in particular their relations with Poisson geometry and general connection theory. It covers much work done since the
Keywords: Lie algebras; Lie groups